Internet-Based Learning Implementation by Certified Teachers: A Case Study at Madrasah Aliyah Negeri Kampar Regency - Idris Harun; Saipuddin Yuliar; Nur Azizah (Ta'dib, 2025)
This study aims to Internet-Based Learning Implementation By Certified Teachers: A Case Study At Madrasah  Aliyah Negeri Kampar Regency. This research is field research using a qualitative approach. The research informants were 12 teachers from 3 Madrasah Aliyah Negeri in Kampar Regency who already have teaching certificates. The data collection techniques used in this study were interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that certified teachers demonstrate professional and pedagogical competence in integrating the internet into the learning process. This is evident from the teachers' ability to design e-learning-based lessons, manage online learning interactions, and monitor the activity and discipline of students through the features of digital learning platforms. Even though it has been certified,  there are still limited infrastructure, uneven internet access, lack of advanced training, limited digital device facilities, so that some certified teachers use professional skills to buy supporting devices.